Promises on the go: A field study on keeping one's word - Kanngiesser, Patricia; Serko, Daniil; Woike, Jan K. (Frontiers in Psychology, 2023)
Promises are voluntary commitments to perform a future action and are often thought to be powerful levers for behavioural change. Here we studied the effectiveness of promises in two preregistered, incentivized field experiment with German students (N = 406) on the premises of a cafeteria. In Experiment 1, the majority of participants (63%) kept their promise to pay back at least half of an €4-endowment, even though there was no foreseeable cost of breaking the promise, reputational or otherwise. Significantly fewer participants (22%) paid back money in a control group that faced a simple choice to return money. In Experiment 2, the majority of participants (54%) kept their promise to mail back a postcard within a week. We found similar return rates (52%) for a second group for which the word ”promise” was omitted from the commitment. Our findings show that participants kept their word outside the laboratory while pursuing everyday activities even when there are no foreseeable negative consequences for breaking it, demonstrating that promises are effective levers for behavioural change.